Bacterial DNA methyltransferase: A key to the epigenetic world with lessons learned from proteobacteria - Gao, Qun; Lu, Shuwei; Wang, Yuwei; He, Longgui; Wang, Mingshu; Jia, Renyong; Chen, Shun; Zhu, Dekang; Liu, Mafeng; Zhao, Xinxin; Yang, Qiao; Wu, Ying; et al. (Frontiers in Microbiology, 2023)
Epigenetics modulates the expression levels of various important genes in both prokaryotes and eukaryotes. Epigenetic traits are heritable without any change in DNA sequence of the genes. DNA methylation is a universal mechanism of epigenetic regulation in all kingdoms of life. In bacteria, DNA methylation is the main form of epigenetic regulation and plays important roles in affecting clinically relevant phenotypes such as virulence, host colonization, sporulation, biofilm formation. In this review, we surveyed bacterial epigenomic studies and focuses on the recent developments in structure, function, and mechanism of several highly conserved bacterial DNA methylases. These methyltransferases are rather common in bacteria and participate in gene expression regulation and chromosomal DNA replication and repair control. Recent advances in sequencing techniques capable of detecting methylation signals have enabled a closer look and characterization of genome-wide epigenetic regulation. With their involvement in critical cellular processes, these highly conserved DNA methyltransferases may emerge as promising targets for the development of novel epigenetic inhibitors for biomedical applications.